The Effect of Acupuncture Therapy on Blood Pressure Changes in Hypertensive Patients with Middle Jiao Dampness-Phlegm Accumulation Syndrome - Cicillia Ari Setyorini Sudarmadi; Stefanus Aditya; Anis Lupita Ningrum (Indonesian Journal of Acupuncture, 2026)
Hypertension is a primary cause of global premature mortality, with a significant burden in low- and middle-income countries where treatment access remains limited. This pre-experimental quantitative study investigated the effect of acupuncture therapy on blood pressure in hypertensive patients diagnosed with Middle Jiao dampness-phlegm accumulation syndrome. Employing a one-group pretest-posttest design, 20 subjects aged 30-40 were selected via purposive sampling at the Sumber Sehat Acupuncture Foundation in Bandung (March-June 2025). The intervention consisted of daily acupuncture sessions over six days. Blood pressure measurements were taken pre- and post-intervention. Pre-test results showed the highest systolic pressure was 139 mmHg and the lowest was 130 mmHg. Post-intervention, the highest systolic pressure decreased to 130 mmHg and the lowest to 120 mmHg. Diastolic pressure also declined from a pre-intervention high of 89 mmHg to a post-intervention high of 85 mmHg. Statistical analysis using the Paired Sample T-Test confirmed a significant difference between pre- and post-intervention measurements (p-value < 0.05), with a mean systolic reduction of 9.50 mmHg and a mean diastolic reduction of 4.55 mmHg. It is concluded that acupuncture therapy significantly influences blood pressure, demonstrating a statistically meaningful effect in patients with this specific syndrome.